Dzienniki stanu pandemii – projekt badawczy, perspektywa teoretyczno-metodologiczna, wyniki badań - Gumuła, Wiesław; Bogunia-Borowska, Małgorzata; Janiszewska, Joanna (Człowiek i Społeczeństwo, 2023)
The article presents the research project “Pandemic diaries” carried out by a team working under the scientific supervision of prof. Wiesław Gumuła. The project was implemented in cooperation with the Institute of Literature in Krakow, which in 2020 announced a literary competition for journals that were to be devoted to everyday life in pandemic conditions. Researchers adopted the theoretical perspective of the sociology of everyday life and the phenomenological one. The analysis concerned the categories appearing in dailies such as social change, social relations, time, death, tourism, economy and economy, and many others. The diaries have literary value and contain important social content that has become the subject of sociological analyzes broadening the knowledge about people’s lives in conditions of sudden and unexpected change.